PENGARUH CARA PENGERINGAN TERHADAP AKTIVITAS MAKANDAN DAYA DAYA HIDUP RAYAP KAYU KERING CRYPTOTERMES CYNOCEPHALUS LIGHT - Agus Ismanto; Ginuk Sumarni (Jurnal Penelitian Hasil Hutan, 1992)
This paper is  dealing with  the  influence  of drying  methods  to feeding  activity  and survival of Cryptotermes  cynoce- phalus   drywood  termite.  The  result  shows   that   drying   methods  have  an  effect on  feeding activity  and  survival of C.  cynocephalus.   Besides  the  drying   methods,  wood  species  has also  an  effect   on  such  both  factor. The  oven method is  more  advantageorus than  desicator  method   which  is  more  selective  and more practice.